Clinical Value and Role of miR-129-5p in Non-Alcoholic Fatty Liver Disease - Wang, Yuan; Feng, Yujia; Zhang, Han; Niu, Qinghui; Liang, Kun; Bian, Cheng; Li, Hong (Hormone and Metabolic Research, 2021)
This study was to evaluate the expression of miR-129–5p in non-alcoholic fatty liver (NAFLD) patients and its clinical value and explore its regulatory effect on insulin resistance (IR). A total of 117 NAFLD patients and 110 healthy controls were included. The levels of miR-129-5p were detected by qRT-PCR. To assess the diagnostic value of miR-129-5p for NAFLD, the receiver operating characteristic curve (ROC) was established. C57Bl/6 mice were supplied with high-fat diet to establish NAFLD model. Intraperitoneal insulin tolerance test (IPITT) was carried out to evaluate the effect of miR-129-5p on IR in NAFLD animal model. miR-129-5p was highly expressed in the serum of NAFLD patients, and patients with HOMA-IR ≥2.5 had higher level of miR-129-5p than those with HOMA-IR <2.5. miR-129-5p had the ability to differentiate NAFLD patients from healthy individuals and might be associated with the development of IR. Serum miR-129-5p was positively correlated with the levels of HOMA-IR, BMI, total cholesterol (TC), and triglyceride (TG) in NAFLD patients. Downregulation of miR-129-5p regulates lipid metabolism and insulin sensitivity in NAFLD mice model. MiR-129-5p was upregulated in NAFLD patients and might be a potential diagnostic biomarker. The regulatory effect of miR-129-5p on NAFLD may function by regulating lipid accumulation and insulin sensitivity.
Keywords: non-alcoholic fatty liver disease; insulin resistance; microRNA-129-5p; HOMA-IR